Ten-Year Average Full Follow-up and Evaluation of a Contoured Focal Resurface Prosthesis (HemiCAP) in Patients in the United Kingdom - Nahas, Sam; Monem, Mohammed; Li, Lily; Patel, Akash; Parmar, Harish (The Journal of Knee Surgery, 2019)
A significant number of patients are affected by localized articular damage that is appropriate neither for traditional arthroplasty nor for biological repair. A focal resurfacing system using a matched contoured articular prosthetic (HemiCAP) has been introduced for the treatment of such cases. Independent long-term results of these implants are limited. We retrospectively evaluated the use of this resurfacing system in 14 patients (13 males, 1 female), with a mean age of 40.3 years (range: 28–49), with focal femoral condyle defects. The same consultant orthopaedic surgeon performed all procedures. Our primary outcome measure was revision rate. Secondary outcome measures included radiographic evaluation (prosthesis migration signs, radiolucency), patient-reported functional evaluation (knee injury and osteoarthritis outcome scores), and complications. A total of 10 patients were treated on the medial femoral condyle, 2 were treated on the lateral condyle, and 2 received bicondylar implants (14 in total). Average follow-up was 107 months (range: 59–135). Three patients were lost to follow-up at the time of study. One patient was excluded from the study. Of the 10 left, 2 had to be revised, leading the survival rate to be 80% at 9.4 years. In four contactable patients, average Knee injury and Osteoarthritis Outcomes score at 121 months postsurgery (9.75 years) was 92.9 (as compared with 57.7 preoperatively). There were no complications. This series demonstrates that focal resurfacing is a safe, suitable, and useful temporizing step in knee arthroplasty surgery. The use of the focal resurfacing implant in this way allows the delay in transition to knee arthroplasty. This series shows an excellent functional outcome for remaining implants at average 10 years, with low complication rates.
Keywords: HemiCAP; osteochondral plug; osteoarthritis; knee